Real-life experience in the treatment of intrahepatic cholangiocarcinoma by 90Y radioembolization: a multicenter retrospective study - Schaarschmidt, Benedikt Michael Sebastian; Kloeckner, Roman; Dertnig, Thomas; Demircioglu, Aydin; Müller, Lukas; Auer, Timo Alexander; Santos, Daniel Pinto dos; Wagner, Verena; Miederer, Matthias; Gebauer, Bernhard; Radunz, Sonia; Kasper, Stefan; et al. (Journal of nuclear medicine, 2023)
Limited treatment options in patients with intrahepatic cholangiocarcinoma (iCCA) demand the introduction of new, catheter-based treatment options. Especially, 90Y radioembolization may expand therapeutic abilities beyond surgery or chemotherapy. Therefore, the purpose of this study was to identify factors associated with an improved median overall survival (mOS) in iCCA patients receiving radioembolization in a retrospective study at 5 major tertiary-care centers. Methods: In total, 138 radioembolizations in 128 patients with iCCA (female, 47.7%; male, 52.3%; mean age ± SD, 61.1 ± 13.4 y) were analyzed. Clinical data, imaging characteristics, and radioembolization reports, as well as data from RECIST, version 1.1, analysis performed 3, 6, and 12 mo after radioembolization, were collected. mOS was compared among different subgroups using Kaplan–Meier curves and the log-rank test. Results: Radioembolization was performed as first-line treatment in 25.4%, as second-line treatment in 38.4%, and as salvage treatment in 36.2%. In patients receiving first-line, second-line, and salvage radioembolization, the disease control rate was 68.6%, 52.8%, and 54.0% after 3 mo; 31.4%, 15.1%, and 12.0% after 6 mo; and 17.1%, 5.7%, and 6.0% after 1 y, respectively. In patients receiving radioembolization as first-line, second-line, and salvage treatment, mOS was 12.0 mo (95% CI, 7.6–23.4 mo), 11.8 mo (95% CI, 9.1–16.6 mo), and 8.4 mo (95% CI, 6.3–12.7 mo), respectively. No significant differences among the 3 groups were observed (P = 0.15). Hepatic tumor burden did not significantly influence mOS (P = 0.12). Conclusion: Especially in advanced iCCA, second-line and salvage radioembolization may be important treatment options. In addition to ongoing studies investigating the role of radioembolization as first-line treatment, the role of radioembolization in the later treatment stages of the disease demands further attention.
Online veröffentlicht: 3. November 2022
Im Titel ist die Zahl 90 hochgestellt
Gesehen am 15.08.2023